High-entropy alloy hydrogen permeation film and preparation method and application thereof
Through the design of the high-entropy alloy layer, the two-phase structure of the BCC-Nb primary phase and eutectic phase is formed by using the multi-component mutual submergence of Nb, Hf, Co, Mo and Ni, W, and Cu elements, and the existing Nb group is solved The problem of the alloy hydrogen permeation film being easily brittle and broken has improved hydrogen permeation and anti-hydrogen embrittlement properties, achieving excellent comprehensive performance and reduced cost of high-entropy alloy hydrogen permeation film.
Patent Information
- Application Number
- CN202411166204.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-01-17
AI Technical Summary
The existing Nb-based alloy hydrogen permeability film has high hydrogen permeability but is easily brittle and has poor overall performance. It has a partially amorphous structure with a two-phase structure with hydrogen permeability and hydrogen embrittlement resistance, and has a low hydrogen permeability coefficient.
The high-entropy alloy layer is used to dissolve multiple components of Nb, Hf, Co, Mo and Ni, W, and Cu elements to promote the formation of primary phase and eutectic phase, and optimize hydrogen permeability and anti-hydrogen embrittlement properties by adjusting the element ratio to form The two-phase structure of the primary phase and the eutectic phase of BCC-Nb avoids the formation of intermetallic compounds.
The hydrogen permeability and hydrogen embrittlement resistance of the hydrogen permeability film are significantly improved, and the comprehensive performance of the high-entropy alloy hydrogen permeability film is achieved is excellent, the application cost is reduced, and mechanical stability is maintained at lower temperatures.
Smart Images

Figure CN119320923A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of hydrogen permeable membranes, and in particular to a high entropy alloy hydrogen permeable membrane and a preparation method and application thereof. Background Art
[0002] VB metal films have excellent hydrogen permeability and low price, and have become the research focus of hydrogen permeable films. Currently reported Nb-based alloys, such as Nb-Ti-Ni alloys, have a primary phase bcc-Nb and a binary eutectic phase {(Nb,Ti)+TiNi}. Since the volume fraction of the primary phase bcc-Nb that plays a hydrogen permeation role is higher than the volume fraction of the binary eutectic phase {(Nb,Ti)+TiNi} that plays a role in hydrogen embrittlement resistance, the hydrogen permeable film has a high hydrogen permeability, but it is prone to hydrogenation and brittle fracture, so the overall performance is poor. Therefore, it is urgent to provide a high entropy alloy hydrogen permeable film with excellent comprehensive performance. Summary of the invention
[0003] The present invention is based on the inventor's discovery and understanding of the following facts and problems: Currently reported Nb-based alloys, such as Nb-Ti-Ni alloys, have high hydrogen permeability, but are prone to hydrogenation and brittle fracture, and have poor overall performance. Some Nb-based alloys are amorphous structures, do not have a two-phase structure of hydrogen permeation and hydrogen embrittlement resistance, and have low hydrogen permeability coefficients.
[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the embodiments of the present invention provide a high entropy alloy hydrogen permeable film and a preparation method and application thereof. The high entropy alloy layer can avoid the formation of intermetallic compounds by multi-component dissolution of Nb, Hf, Co and Mo elements and Ni, W, and Cu elements, promote the formation of primary phases in the hydrogen permeable film, and effectively improve the hydrogen permeability of the hydrogen permeable film. By adding Ni, W, and Cu elements, the formation of eutectic phase in the hydrogen permeable film is promoted, the volume fraction of eutectic phase is increased, and the hydrogen embrittlement resistance of the hydrogen permeable film is effectively improved.
[0005] The embodiment of the present invention provides a high entropy alloy hydrogen permeable film, wherein the high entropy alloy hydrogen permeable film comprises a high entropy alloy layer, wherein the chemical formula of the high entropy alloy layer is Nb 100-(a+b+c+d) Hf a Co b Mo c -M d , M is selected from at least one of Ni, W and Cu elements, 5≤a≤35, 5≤b≤35, 5≤c≤30, 5≤d≤35.
[0006] Advantages and technical effects of the high entropy alloy hydrogen permeable film of the embodiment of the present invention: The high entropy alloy layer can avoid the formation of intermetallic compounds through the mutual dissolution of Nb, Hf, Co and Mo elements and Ni, W, Cu elements, promote the formation of primary phases in the hydrogen permeable film, and effectively improve the hydrogen permeability of the hydrogen permeable film. By adding Ni, W, and Cu elements, the formation of eutectic phase in the hydrogen permeable film is promoted, the volume fraction of eutectic phase is increased, and the hydrogen embrittlement resistance of the hydrogen permeable film is effectively improved.
[0007] In some embodiments, characteristic parameters of the high entropy alloy layer simultaneously satisfy the following ranges: VEC≥5.5, Delta>6.6, 1.0≤Ω≤1.5.
[0008] In some embodiments, the high entropy alloy layer includes Nb 35 Hf 15 Co 33 Mo 7 W 10 , Nb 35 Hf 15 Co 33 Mo 7 Cu 10 , Nb 35 Hf 28 Co 17 Mo 5 Ni 15 At least one of .
[0009] In some embodiments, the thickness of the high entropy alloy layer is 0.6-0.8 mm.
[0010] In some embodiments, the high entropy alloy hydrogen permeable film further includes a Pd layer, and the Pd layer is disposed on both sides of the high entropy alloy layer along the thickness direction thereof.
[0011] In some embodiments, the thickness of the single-sided Pd layer is 10-500 nm.
[0012] The present invention provides a method for preparing a high entropy alloy hydrogen permeable film, comprising the following steps:
[0013] (1) preparing raw materials according to the proportion of the high entropy alloy layer, and smelting the raw materials to obtain a master alloy ingot;
[0014] (2) Cutting the master alloy ingot into alloy sheets, grinding, polishing and cleaning the alloy sheets to obtain a high entropy alloy layer.
[0015] In some embodiments, a Pd layer is plated on the surface of the high entropy alloy layer to obtain a high entropy alloy hydrogen permeable film.
[0016] In some embodiments, the Pd layer is deposited using a magnetron sputtering technique.
[0017] The embodiment of the present invention provides an application of a high entropy alloy hydrogen permeable membrane for separation of hydrogen-doped natural gas, purification and / or refining of hydrogen, and separation of deuterium and tritium. The embodiment of the present invention has all the advantages of a high entropy alloy hydrogen permeable membrane, which will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 These are pictures of the high entropy alloy master alloy ingot and the high entropy alloy hydrogen permeable film of Example 1. DETAILED DESCRIPTION
[0019] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0020] A high entropy alloy hydrogen permeable film according to an embodiment of the present invention comprises a high entropy alloy layer, wherein the chemical formula of the high entropy alloy layer is Nb 100-(a+b+c+d) Hf a Co b Mo c -M d , M is selected from at least one of Ni, W and Cu elements, 5≤a≤35, 5≤b≤35, 5≤c≤30, 5≤d≤35.
[0021] The high entropy alloy hydrogen permeable film of the embodiment of the present invention, the high entropy alloy refers to a solid solution alloy formed by 5 or more elements (the atomic percentage of each component is between 5% and 35%), the hydrogen permeable film in the present application adopts a high entropy alloy, and the high entropy alloy layer can avoid the formation of intermetallic compounds through the mutual dissolution of Nb, Hf, Co and Mo elements and Ni, W, Cu elements, promote the formation of primary phases in the high entropy alloy hydrogen permeable film, and effectively improve the hydrogen permeability of the hydrogen permeable film. By adding Ni, W, and Cu elements, the formation of eutectic phase in the hydrogen permeable film is promoted, the volume fraction of eutectic phase is increased, and the hydrogen embrittlement resistance of the hydrogen permeable film is effectively improved.
[0022] Class A elements represent elements that react easily with hydrogen, i.e. hydrogen-absorbing elements, and Nb and Hf are Class A elements; Class B elements represent elements that react poorly with hydrogen, i.e. hydrogen-repelling elements, and Co, Mo, Ni, W, and Cu are Class B elements. The combination of NbHfCoMo-M elements is beneficial to improving hydrogen permeability and hydrogen embrittlement resistance. Among them, the VIB group Mo element of the VB group Nb element neighbor group is a hydrogen-repelling element, and can form an infinitely miscible solid solution with Nb. The presence of Mo can not only greatly reduce the hydrogen dissolution of the alloy, but also, an appropriate amount of Mo can optimize the diffusion path of hydrogen in Nb and reduce its diffusion barrier. Mo replaces Nb to reduce hydrogen dissolution, which improves the alloy's hydrogen embrittlement resistance to a certain extent. When the Mo content is low, the alloy still has a greater tendency to hydrogen embrittlement, but once the Mo content is high, the hydrogen permeability of the alloy is greatly reduced, so the Mo content is preferably 5≤c≤30. By adjusting the content of A-type elements Nb and Hf, it is beneficial to the formation of BCC-Nb primary phase in the high entropy alloy hydrogen permeation film, increasing the volume fraction of BCC-Nb primary phase, and thus effectively improving the hydrogen permeability of the alloy; by adjusting the content of B-type elements Co, Mo and M, it is beneficial to the formation of eutectic phase in the high entropy alloy hydrogen permeation film, increasing the volume fraction of eutectic phase, and thus effectively improving the hydrogen embrittlement resistance of the alloy; by adjusting the ratio of A and B-type elements, the ratio of BCC-Nb primary phase to eutectic phase can be controlled, and the comprehensive performance can be controlled. By using NbHfCoMo-M as the high entropy alloy layer of the high entropy alloy hydrogen permeation film, the noble metal Pd hydrogen permeation film is replaced, effectively reducing the application cost of the high entropy alloy hydrogen permeation film.
[0023] In the embodiments of the present invention, the NbHfCoMo-M high entropy alloy hydrogen permeable film has a "high entropy effect", "lattice distortion effect", "hysteresis diffusion effect" and "cocktail effect", which are beneficial to improving the hydrogen permeability and hydrogen embrittlement resistance of the alloy film. Compared with the traditional alloy hydrogen permeable film, the advantages of the NbHfCoMo-M high entropy alloy hydrogen permeable film of the present invention are reflected in: (1) The high entropy alloy has a "high entropy effect". Compared with the traditional hydrogen permeable alloy, the high mixing entropy of NbHfCoMo-M is more conducive to promoting the formation of a solid solution phase with good compatibility of multiple alloy elements. The high entropy alloy hydrogen permeable film with a BCC solid solution phase of the present invention has a larger lattice gap of the BCC solid solution phase, which is beneficial to increase the diffusion rate of hydrogen, thereby improving the hydrogen permeability of the high entropy alloy hydrogen permeable film. (2) The "lattice distortion effect" of the NbHfCoMo-M high entropy alloy makes the high entropy alloy hydrogen permeable film have a larger lattice expansion coefficient. Compared with traditional hydrogen permeable alloys, the larger lattice expansion coefficient of NbHfCoMo-M high entropy alloy hydrogen permeable film is more conducive to the transmission of hydrogen and improves the hydrogen diffusion coefficient. In addition, the lattice distortion can also cause the NbHfCoMo-M high entropy alloy hydrogen permeable film to undergo solid solution strengthening, which greatly improves its mechanical properties compared with traditional hydrogen permeable alloys and can improve the hydrogen embrittlement resistance of the high entropy alloy hydrogen permeable film; (3) The "hysteresis diffusion effect" of NbHfCoMo-M high entropy alloy makes the high entropy alloy hydrogen permeable film have the characteristics of slow atomic diffusion rate. Compared with traditional hydrogen permeable alloys, the slow diffusion rate of alloying elements in high entropy alloy hydrogen permeable films is conducive to maintaining a stable phase structure of the alloy film, thereby enabling it to maintain good mechanical stability under hydrogen-containing working conditions and improving the hydrogen embrittlement resistance of high entropy alloy hydrogen permeable films. (4) Based on the "cocktail effect" characteristics of NbHfCoMo-M high entropy alloy, by changing the type and proportion of type A elements and type B elements, the hydrogen solid solubility, hydrogen diffusion coefficient and hydrogen embrittlement resistance of the high entropy alloy hydrogen permeable films can be regulated, which can effectively improve the hydrogen permeability and hydrogen embrittlement resistance of the high entropy alloy hydrogen permeable films.
[0024] In some embodiments, a, b, c, and d are all mole percentage contents:
[0025] 5≤a≤35, specifically, for example, 5, 10, 15, 20, 25, 30, 35, optionally, 10≤a≤30;
[0026] 5≤b≤35, specifically, for example, 5, 10, 15, 20, 25, 30, 35, optionally, 10≤b≤35;
[0027] 5≤c≤30, specifically, for example, 5, 7, 10, 15, 30, optionally, 5≤c≤15, preferably, 5≤c≤10;
[0028] 5≤d≤35, specifically, for example, 5, 10, 15, 20, 25, 30, 35, optionally, 5≤d≤25.
[0029] In the embodiments of the present invention, by adjusting the content of each element, it is beneficial to further improve the hydrogen permeability and hydrogen embrittlement resistance of the high entropy alloy hydrogen permeable film.
[0030] In some embodiments, characteristic parameters of the high entropy alloy layer simultaneously satisfy the following ranges: VEC≥5.5, Delta>6.6, 1.0≤Ω≤1.5.
[0031] In the embodiments of the present invention, the characteristic parameters will significantly affect the phase structure and hydrogen permeation performance of the high entropy alloy.
[0032] VEC stands for valence electron concentration, which is the total number of electrons in the outer shell of an atom. The definition of VEC is as follows:
[0033]
[0034] Where, VEC i represents the valence electron concentration of element i, c i represents the atomic fraction of element i.
[0035] The VEC of the high entropy alloy layer will affect the hydrogen embrittlement resistance of the hydrogen permeable film. The VEC value can be changed by adjusting the type and content of metal elements in the high entropy alloy. As the VEC decreases, the hydrogen solubility of the alloy gradually increases. The alloy is prone to hydrogen embrittlement due to more dissolved hydrogen, which is not conducive to the alloy's hydrogen embrittlement resistance. Therefore, when the VEC of the high entropy alloy layer of the high entropy alloy hydrogen permeable film of the present invention is not less than 5.5, it is beneficial to control the hydrogen solubility of hydrogen in the alloy and improve the hydrogen embrittlement resistance.
[0036] Delta means atomic size mismatch. The definition of Delta is as follows:
[0037]
[0038] In the formula, r i represents the atomic radius of element i; c i represents the atomic fraction of element i; is the average atomic radius.
[0039] Delta affects the phase structure of the hydrogen permeation film. By adjusting the value of Delta, the crystal structure can be changed to have a multiphase structure. The hydrogen permeation high entropy alloy layer needs to satisfy the multiphase structure to comprehensively exert the hydrogen permeation performance and hydrogen embrittlement resistance at the same time. When Delta is less than 6.6, its crystal structure is a single-phase structure. Therefore, when the high entropy alloy of the present invention satisfies Delta>6.6, it is conducive to forming a multiphase structure, obtaining a hydrogen permeation phase and an anti-hydrogen phase, and improving the hydrogen permeation performance and hydrogen embrittlement resistance.
[0040] Ω means mixing entropy, mixing enthalpy and melting point related parameters Ω. The definition of Ω is shown in the following formula:
[0041]
[0042] In the formula, c i and c j is the atomic fraction of elements i and j; H ij is the mixing enthalpy of elements i and j at equimolar concentrations in a binary solution; Ln is the logarithm with the irrational number e as the base; (T m ) i is the melting temperature of element i; R is the ideal gas constant.
[0043] Ω will affect the performance of the hydrogen permeable film, and the value of Ω can be changed by adjusting the type and content of metal elements. When Ω≤1, the mixing enthalpy is the dominant term of Gibbs free energy, and therefore tends to stabilize intermetallic compounds, ordered phases or multiphases. If Ω>1, the dominant term of Gibbs free energy is the mixing entropy, and there is a tendency to form a disordered solid solution. For the determination of the relevant parameters Ω of the high entropy alloy hydrogen permeable film of the present invention, on the one hand, in order to avoid the formation of intermetallic compounds, Ω>1 should be satisfied, and the alloy forms a disordered solid solution; on the other hand, in order to avoid the complete solid solution of the alloy elements to form a single phase, Ω cannot be too large. Therefore, in order to meet the requirements of the alloy phase, 1.0≤Ω≤1.5 is beneficial to improving the hydrogen permeability and hydrogen embrittlement resistance.
[0044] In some embodiments, the high entropy alloy layer includes Nb 35 Hf 15 Co 33 Mo 7 W 10 , Nb 35 Hf 15 Co 33 Mo 7 Cu 10 , Nb 35 Hf 28 Co 17 Mo 5 Ni 15 In the embodiment of the present invention, by optimizing the composition of the high entropy alloy layer, it is beneficial to further improve the hydrogen permeability and hydrogen embrittlement resistance of the high entropy alloy hydrogen permeable film.
[0045] In some embodiments, the alloy material includes a two-phase structure of a hydrogen permeation phase and a hydrogen embrittlement resistance phase. Specifically, the two-phase structure includes a BCC-Nb primary phase and a binary eutectic phase. In the embodiment of the present invention, the BCC-Nb primary phase plays a hydrogen permeation role, that is, a hydrogen permeation phase; the eutectic phase plays an anti-hydrogen embrittlement role, that is, an anti-hydrogen embrittlement phase.
[0046] In some embodiments, the thickness of the high entropy alloy layer is 0.6-0.8 mm, specifically, for example, 0.6 mm, 0.65 mm, 0.7 mm, 0.75 mm, 0.8 mm.
[0047] In some embodiments, the high entropy alloy hydrogen permeable film further comprises a Pd layer, and the Pd layer is disposed on both sides of the high entropy alloy layer along the thickness direction thereof. In the embodiment of the present invention, the Pd layer is plated on the surface to prevent the NbHfCoMo-M alloy from being oxidized by impurity gases such as NO, H 2 S.O. 2 The hydrogen permeability and hydrogen embrittlement resistance of high entropy alloy hydrogen permeable film can be effectively improved.
[0048] In some embodiments, the thickness of the Pd layer is 10-500nm, and optionally, the thickness of the single-sided Pd layer is 10-500nm, specifically, for example, 10nm, 20nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm. In the embodiment of the present invention, the thickness of the Pd film is selected in the range of 10-500nm. The thickness of the Pd film is not easy to be too thin. If it is too thin, the surface of the Nb-based intermediate layer cannot be completely covered due to Pd diffusion, and it is difficult to play its anti-poisoning role. If it is too thick, the overall cost of the hydrogen permeation membrane will be too high.
[0049] In some embodiments, the hydrogen permeability coefficient of the high entropy alloy hydrogen permeable film at 400° C. is 3.0×10 -8 -8×10 -8 mol H 2 m -1 s -1 Pa -0.5 .
[0050] In some embodiments, the temperature at which the high entropy alloy hydrogen permeable film undergoes hydrogen embrittlement rupture is lower than 150°C. In an embodiment of the present invention, during the hydrogen embrittlement resistance test, as the test temperature gradually decreases, the hydrogen absorption of the hydrogen permeable film gradually increases, and hydrogen embrittlement is more likely to occur, which will cause hydrogen embrittlement rupture of the high entropy alloy hydrogen permeable film. The temperature at which the high entropy alloy hydrogen permeable film of the present invention undergoes hydrogen embrittlement rupture is lower than 150°C, and hydrogen embrittlement rupture can still be prevented at a lower temperature.
[0051] A method for preparing a high entropy alloy hydrogen permeable film according to an embodiment of the present invention comprises the following steps:
[0052] (1) preparing raw materials according to the proportion of the high entropy alloy layer, and smelting the raw materials to obtain a master alloy ingot;
[0053] (2) Cutting the master alloy ingot into alloy sheets, grinding, polishing and cleaning the alloy sheets to obtain a high entropy alloy layer.
[0054] In some embodiments, in step (1), the raw material is melted; optionally, the vacuum degree of the melting is 3-7×10 -3 Pa; the smelting is carried out in a vacuum melting furnace, optionally, a vacuum arc melting furnace; the smelting is repeated 3-8 times, specifically, for example, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times; the smelting current is 100-500A, specifically, for example, 100A, 200A, 300A, 400A, 500A.
[0055] In some embodiments, in the step (2), the master alloy ingot is cut into alloy sheets by wire cutting, and the alloy sheets are ground, polished and cleaned; optionally, the wire cutting adopts an electric spark CNC wire cutting machine; the alloy sheet is circular; the diameter of the alloy sheet is 10-20 mm; the thickness of the alloy sheet is 0.8-1.0 mm; the grinding adopts silicon carbide sandpaper; the silicon carbide sandpaper is selected from at least one of 150#, 240#, 600#, 800#, 1200#, 2000# and 3000# silicon carbide sandpaper, optionally, the grinding is carried out in the order of small mesh number to large mesh number using 150#, 240#, 600#, 800#, 1200#, 2000# and 3000# silicon carbide sandpaper; the polishing treatment adopts polishing paste; the cleaning adopts anhydrous ethanol; the cleaning adopts ultrasonic cleaning. In the embodiment of the present invention, the grinding is carried out in sequence from small mesh to large mesh using silicon carbide sandpaper, which is beneficial to eliminating surface scratches.
[0056] In some embodiments, a Pd layer is plated on the surface of the high entropy alloy layer to obtain a high entropy alloy hydrogen permeable film. Optionally, the Pd layer is plated using magnetron sputtering technology; optionally, the sputtering power is 25-300W, specifically, for example, 25W, 50W, 100W, 150W, 200W, 250W, 300W.
[0057] The application of a high entropy alloy hydrogen permeable membrane in an embodiment of the present invention is used for separation of hydrogen-doped natural gas, purification and / or refining of hydrogen, and separation of deuterium and tritium. In the embodiment of the present invention, all the advantages of the high entropy alloy hydrogen permeable membrane are possessed, which will not be described in detail here.
[0058] In some embodiments, the deuterium-tritium separation is nuclear fusion fuel deuterium-tritium separation.
[0059] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0060] Example 1
[0061] A Nb 35 Hf 15 Co33 Mo 7 W 10 A method for preparing a Pd high entropy alloy hydrogen permeable film comprises the following steps:
[0062] (1) The raw materials with a purity of ≥99.9% are mixed according to the chemical composition ratio of the high entropy alloy layer. The chemical formula of the high entropy alloy layer is Nb 100-(a+b+c+d) Hf a Co b Mo c -M d , a, b, c, d are the mole percentages of each component, and a=15, b=33, c=7, d=10, M is W;
[0063] (2) The raw material is placed in a vacuum of 3×10 -3 Pa vacuum arc melting furnace for 5 times with a melting current of 400A to obtain a master alloy ingot with uniform composition, such as Figure 1 As shown in the left picture;
[0064] (3) using an electric spark CNC wire cutting machine to cut the master alloy ingot into round alloy sheets with a diameter of 20 mm and a thickness of 0.8 mm;
[0065] (4) The circular alloy sheet was polished flat using 150#, 240#, 600#, 800#, 1200#, 2000# and 3000# silicon carbide sandpaper in sequence, and the alloy film was polished with polishing paste to remove surface scratches, and finally ultrasonically cleaned with anhydrous ethanol to obtain a high entropy alloy layer with a thickness of 0.6 mm; the characteristic parameters of the high entropy alloy layer were VEC of 6.34, Delta of 8.00, and Ω of 1.45;
[0066] (5) Place the high entropy alloy layer on the center of the sample stage of the magnetron sputtering equipment, close the reaction chamber, and evacuate to 1.0×10 -4 Pa. Argon gas was introduced at a flow rate of 20 sccm to make the pressure in the reaction chamber about 1.0 Pa. The sample stage speed was set to 15 r / min and the sample stage temperature was set to 300 °C. When the sample stage temperature reached the set temperature, the Pd surface layer was sputtered. The initial sputtering power of the Pd target was set to 150 W. The Pd target was turned on to start sputtering. After the sputtering time was 10 minutes, the Pd target sputtering power was turned off.
[0067] The thickness of the Pd layer on one side is 100nm. The same method is used to plate the other side. After plating on both sides, Nb 35 Hf 15 Co 33 Mo 7 W 10-Pd high entropy alloy hydrogen permeable film, such as Figure 1 As shown in the picture on the right.
[0068] Example 2
[0069] A Nb 35 Hf 15 Co 33 Mo 7 Cu 10 The preparation method of the -Pd high entropy alloy hydrogen permeable film is the same as the preparation method of Example 1, except that: a=15, b=33, c=7, d=10, and M is Cu. The characteristic parameters VEC of the high entropy alloy layer are 6.84, Delta is 8.37, and Ω is 1.49.
[0070] Example 3
[0071] A Nb 35 Hf 28 Co 17 Mo 5 Ni 15 The preparation method of the high entropy alloy hydrogen permeable film is the same as that of Example 1, except that: a=28, b=17, c=5, d=15, and M is Ni. The characteristic parameters VEC of the high entropy alloy layer are 6.20, Delta is 6.69, and Ω is 1.13.
[0072] Comparative Example 1
[0073] A Nb 25 Hf 33 Co 12 Mo 15 W 15 The preparation method of the -Pd high entropy alloy hydrogen permeable film is the same as the preparation method of Example 1, except that: a=33, b=12, c=15, d=15, and M is W. The characteristic parameters VEC of the high entropy alloy layer are 5.45, Delta is 7.70, and Ω is 2.95.
[0074] Comparative Example 2
[0075] A Nb 20 Hf 35 Co 10 Mo 20 Cu 15 The preparation method of the -Pd high entropy alloy hydrogen permeable film is the same as the preparation method of Example 1, except that: a=35, b=10, c=20, d=15, and M is Cu. The characteristic parameters VEC of the high entropy alloy layer are 6.15, Delta is 8.63, and Ω is 3.43.
[0076] Comparative Example 3
[0077] A Nb 31 Hf 5 Co 25 Mo 30 Ni 9 The preparation method of the -Pd high entropy alloy hydrogen permeable film is the same as the preparation method of Example 1, except that: a=5, b=25, c=30, d=9, and M is Ni. The characteristic parameters VEC of the high entropy alloy layer are 6.70, Delta is 6.58, and Ω is 1.62.
[0078] Table 1
[0079]
[0080]
[0081] The hydrogen permeation performance and hydrogen embrittlement resistance of the hydrogen permeable membranes of the embodiments and comparative examples were tested at different temperatures, the maximum hydrogen permeation coefficient at 400° C. was tested, and a hydrogen embrittlement resistance test was performed.
[0082] Table 2
[0083]
[0084] It can be seen from Table 1 and Table 2 that when the characteristic parameters of the high entropy alloy layer of the high entropy alloy hydrogen permeable membrane in Examples 1-3 simultaneously meet the design range VEC ≥ 5.5, Delta > 6.6, 1.0 ≤ Ω ≤ 1.5, the high entropy alloy hydrogen permeable membrane has a high hydrogen permeability coefficient and strong hydrogen embrittlement resistance, and has excellent comprehensive performance. The maximum hydrogen permeability coefficient at 400 ° C is not less than 4×10 -8 mol H 2 m - 1 s -1 Pa -0.5 In the hydrogen embrittlement resistance test, the hydrogen permeable film did not break above 100°C.
[0085] Comparative Examples 1-3 do not meet VEC≥5.5, Delta>6.6 or 1.0≤Ω≤1.5, and their hydrogen permeation and hydrogen embrittlement resistance are poor, and the maximum hydrogen permeation coefficient at 400°C is less than 3×10 -8 mol H 2 m -1 s -1 Pa -0.5. Specifically, the characteristic parameter VEC of the high entropy alloy layer in Comparative Example 1 is 5.45, and Ω is 2.95. VEC is small, the hydrogen solubility of the alloy increases, and the alloy is prone to hydrogen embrittlement due to more dissolved hydrogen. Ω is large, the degree of solid solution of alloy elements is large, and the hydrogen permeability and hydrogen embrittlement resistance are poor. The characteristic parameter Ω of the high entropy alloy layer in Comparative Example 2 is 3.43, Ω is large, and the hydrogen permeability and hydrogen embrittlement resistance are poor. The characteristic parameter Delta of the high entropy alloy layer in Comparative Example 3 is 6.58, and Ω is 1.62, which is not conducive to obtaining hydrogen permeation phase and hydrogen resistance phase, and the hydrogen permeability and hydrogen embrittlement resistance are poor.
[0086] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0087] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A high entropy alloy hydrogen permeable membrane, characterized in that: The high entropy alloy hydrogen permeable film comprises a high entropy alloy layer, the chemical formula of which is Nb 100-(a+b+c+d) Hf a Co b Mo c -M d , M is selected from at least one of Ni, W and Cu elements, 5≤a≤35, 5≤b≤35, 5≤c≤30, 5≤d≤35.
2. The high entropy alloy hydrogen permeable membrane according to claim 1, characterized in that: The characteristic parameters of the high entropy alloy layer simultaneously satisfy the following ranges: VEC≥5.5, Delta>6.6, 1.0≤Ω≤1.
5.
3. The high entropy alloy hydrogen permeable membrane according to claim 1 or 2, characterized in that: The high entropy alloy layer includes Nb 35 Hf 15 Co 33 7W 10 , Nb 35 Hf 15 Co 33 Mo7Cu 10 , Nb 35 Hf 28 Co 17 Mo5Ni 15 At least one of .
4. The high entropy alloy hydrogen permeable membrane according to claim 1, characterized in that: The thickness of the high entropy alloy layer is 0.6-0.8 mm.
5. The high entropy alloy hydrogen permeable membrane according to claim 1, characterized in that: The high entropy alloy hydrogen permeable film further includes a Pd layer, and the Pd layer is arranged on both sides of the high entropy alloy layer along the thickness direction thereof.
6. The high entropy alloy hydrogen permeable membrane according to claim 5, characterized in that: The thickness of the single-side Pd layer is 10-500 nm.
7. A method for preparing a high entropy alloy hydrogen permeable film according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) preparing raw materials according to the proportion of the high entropy alloy layer, and smelting the raw materials to obtain a master alloy ingot; (2) Cutting the master alloy ingot into alloy sheets, grinding, polishing and cleaning the alloy sheets to obtain a high entropy alloy layer.
8. The method for preparing a high entropy alloy hydrogen permeable film according to claim 7, characterized in that: A Pd layer is plated on the surface of the high entropy alloy layer to obtain a high entropy alloy hydrogen permeable film.
9. The method for preparing a high entropy alloy hydrogen permeable film according to claim 8, characterized in that: The Pd layer was deposited by magnetron sputtering technology.
10. Use of the high entropy alloy hydrogen permeable membrane according to any one of claims 1 to 6 or the high entropy alloy hydrogen permeable membrane prepared by the preparation method according to any one of claims 7 to 9, characterized in that: Used for separation of hydrogen-doped natural gas, purification and / or upgrading of hydrogen, and separation of deuterium and tritium.
Citation Information
Cited By
Composite membrane material as well as preparation method and application thereof
CN121222284A